Eficiência da escada para peixes da UHE Engenheiro Sérgio Motta em transpor Rhinelepis aspera (Spix & Agassiz, 1829): uma abordagem ecohidráulica - Fortunato, Wane Cristina Picanço (2021)
In order to mitigate the effects caused by fragments of the environment, fish transposition systems (STPs) are implemented in hydroelectric dams, in order to restore the structural connectivity of rivers and allow the passage of migrants (functional connectivity), such as the armored catfisher, Rhinelepis aspera, a migratory species that is threatened with extinction, despite having great economic and ecological importance. The study evaluated the fish ladder ladder at HPP Engenheiro Sergio Motta - CESP, from December / 2015 to June / 2016, and evaluated the influence of hydraulic and hydrological variables, the attraction and efficiency of the ladder for fish on the ascent of R. aspera. Use the Radio Frequency Identification (RFID) system, with eight antennas installed along the fish ladder and 32 mm transponders (PIT-tags) that were implanted in the abdominal cavity of 200 adult specimens. To calculate the attractiveness of the stairs, it was considered a percentage of property that the entrance, the transit time and the cumulative transit time between the antenna segments. Hydraulic factors (speed, flow, dissipated power) and hydrological factors (downstream level, ladder level and reservoir level) were used to evaluate an interference in the rise of R. aspera through COX regression analysis. Of the total reserved marked and released downstream of the dam, 71% (142) entered the fish ladder. The time it took R. aspera to enter the fish ladder from the moment of release ranged from 196.71h to 1878.75h. Individuals released on the left margin, where the ladder is, source the highest entry rate (80, 76%). Only 25% moved to the last antenna on the ladder, where they were registered by antenna A8. We conclude that the UHE Porto Primavera fish ladder was supplied to R. aspera, however the transposition system has characteristics and hydraulics that limit the ascent of this species. This was evidenced by the significant reduction in the number of preference between the 3-4 antenna stretches and the reduced transposition of the species. Although the study has important results on the efficiency of the Porto Primavera fish ladder for the studied species, important questions such as swimming capacity, feeding and reproductive behavior of the species in this region still need to be answered.